2019
DOI: 10.3390/en12040647
|View full text |Cite
|
Sign up to set email alerts
|

Energy, CO2, and AQI Efficiency and Improvement of the Yangtze River Economic Belt

Abstract: With the rapid development of its economy, environmental governance is becoming more important in China. The Yangtze River Economic Belt (YREB), as the world’s largest inland shipping channel, can lead the country’s regional green economy development. As most research on China’s environmental efficiency focuses on provinces or the east and west regions, this paper examines its energy input and output and environmental effects from the aspects of YREB and non-YREB, breaking through the limitations of previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The southern coastal economic zone and the eastern coastal comprehensive economic zone is higher than other regions. Ren et al 37 Meta-Frontier dynamic SBM model…”
Section: Camioto Et Al 28mentioning
confidence: 99%
“…The southern coastal economic zone and the eastern coastal comprehensive economic zone is higher than other regions. Ren et al 37 Meta-Frontier dynamic SBM model…”
Section: Camioto Et Al 28mentioning
confidence: 99%
“…Therefore, the YREB has also attracted widespread attention in the academic community. At present, research on the YREB mainly includes urbanization [40][41][42], regional innovation [43][44][45], the ecological environment [46][47][48], and carbon emissions [49][50][51]. In the study of the urbanization in the Yangtze River Economic Belt, specifically speaking, Liu et al [40] explored the relationship between the expansion of urban land use in China's YREB and the scope of human activities.…”
Section: Introductionmentioning
confidence: 99%
“…The results exhibited that the efficiencies of the United Arab Emirates and Singapore are increasing year by year. Ren et al [39] used the meta-frontier dynamic SBM model to explore the energy and emissions efficiencies of the Yangtze River Economic Belt (YREB) in China from 2014 to 2016. Their results showed that YREB's energy and emissions efficiencies are higher than those of non-YREB.…”
Section: Introductionmentioning
confidence: 99%